Evaluation of maxillary first permanent molar periodontal condition after using three types of rapid maxillary expanders (conventional, hybrid and MSE) after6 months in adolescents. Randomized controlled trial - Mohamed Abdelrhman Shendy,; Ahmed Abouelnour,; Mostafa Magdi Abdel Monem Abdel Allah,; Sara Elkabbany,; Mohamed Mohamed Ali,; Ahmed Shehata Mohamed Ammar,; Ibraheem Mahmoud Mwafey,; Hisham Mohamed Abozaid,; Ahmed Mohamed Elshamy,; Hamdy A Abol-Khair,; Ibrahim Sabry El sayed,; Ahmed Mangoud Badr, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objectives: The purpose was to evaluate and measure the impact of three types of maxillary expanders (conventional, hybrid, and maxillary skeletal expander (MSE)on the alveolar bone of the buccal surface of maxillary first permanent molar in adolescents, clinically and by using cone beam computed tomography (CBCT). Material and Methods: Three groups were included during the study, with a final sample of 46 healthy participants (17 girls and 29 boys) aged 11–16 years. Patients were allocated to groups with the aid of sequentially numbered, opaque sealed envelopes (SNOSE). Group A received conventional hyrax appliance (CH) (5 girls, 10 boys), Group B used hybrid hyrax appliance with two anterior palatal miniscrews (HH) (6 girls, 9 boys), and Group C had the maxillary skeletal expander (MSE) (6 girls, 10 boys). Using Anatomage in vivo 5.19, Dental, skeletal and periodontal parameters were investigated for each group at base line (T1) and after expansion(T2), based on 92 CBCT scans. Results: Comparisons of normally distributed numerical variables between groups were conducted using ANOVA, then post hoc test (Bonferroni)when the difference was foundand significant. Comparison of baseline and post-treatment values through using the paired t-test.The results of the randomized controlled trial revealed significant variations in the periodontal conditions associated with the three types of rapid maxillary expanders. Specifically, the study demonstrated that the Conventional expander presented more adverse effects on periodontal health ofupper first permanent molars compared to the Hybrid and MSE. Conclusion: Instead of being influenced by the type of expansion appliance, the plaque index increased, and the buccal bone thickness decreased. However, the MARPE, especially the MSE, may show less buccal bone resorption in relation to the conventional hyrax appliance.